Cells isolated from regenerating caudal fin of Sparus aurata can differentiate into distinct bone cell lineages - Vijayakumar, Parameswaran (2021)
Teleosts have the ability to regenerate their caudal fin upon amputation. A highly proliferative mass of undifferentiated cells called blastema forms beneath wound epidermis and differentiates to regenerate all missing parts of the fin. To date, the origin and fate of the blastema is not completely understood. However, current hypotheses suggest that the blastema is comprised of lineage-restricted dedifferentiated cells. To investigate the differentiation capacity of regenerating fin-derived cells, primary cultures were initiated from the explants of 2-days post-amputation (dpa) regenerates of juvenile gilthead seabream (Sparus aurata). These cells were subcultured for over 30 passages and were named as BSa2. After 10 passages they were characterized for their ability to differentiate towards different bone cell lineages and mineralize their extracellular matrix, through immunocytochemistry, histology, and RT-PCR. Exogenous DNA was efficiently delivered into these cells by nucleofection. Assessment of lineage-specific markers revealed that BSa2 cells were capable of osteo/chondroblastic differentiation. BSa2 cells were also found to be capable of osteoclastic differentiation, as demonstrated through TRAP-specific staining and pit resorption assay. Here, we describe the development of the first successful cell line viz., BSa2, from S. aurata 2-dpa regenerating caudal fins, which has the ability of multilineage differentiation and is capable of in vitro mineralization. The availability of such in vitro cell systems has the potential to stimulate research on the mechanisms of cell differentiation during fin regeneration and provide new insights into the mechanisms of bone formation.